Huquq al-Nabi salla Allah 'alayh wa-sallam min manzur Qur'ani : dirasah waqi'iyah = Rights of the Prophet (SAW) from Quranic view : a contemporary study / Bassam Abdulmajid Abdullah Alromema - Alromema, Bassam Abdulmajid Abdullah (2012)
The rights of the Prophet (salla Allah alaih wa sallam) Allah has certainly made obligatory on the Ummah (Muslim nation). When the Muslim Ummah adhered to these rights and complied to his commandments, Allah provided them with empowerment over Earth. So, it was the best Ummah has ever created and was also strong and respected by the others. However, that who observes the reality of Islamic Ummah this time will find that there is a shortcoming and avoidance of, and negligence and exaggeration in the Prophet’s great rights. Therefore, the it is important to talk about this subject because there is an immense benefit represented in performing his rights as Allah wanted. The objectives are mentioning the most outstanding rights such as love, obedience, following and support, uncovering those who are rough and extremist in dealing with the Prophet (salla Allah alaih wa sallam), non-Muslims’ attitude from the Prophet (salla Allah alaih wa sallam), and mentioning the reasons why the West attacks him. According to the findings in the research, I found that the Prophet (salla Allah alaih wa sallam)’s rights have to be performed as Allah commanded us without extremism or avoidance in dealing with our Prophet (salla Allah alaih wa sallam), and that the methodology of Ahl-us-Sunnah is the true methodology which must be conducted, and that the untrue groups such as Al-Rafidhah (the Refusers) and extremist Sufis have disagreed with true methodology in dealing with the beloved Prophet (salla Allah alaih wa sallam). It is incumbent upon Muslims to support the Prophet (salla Allah alaih wa sallam), and boycott any who misbehaves with him until he quits his misbehaviour. The repetition of that misbehavior against the Prophet (salla Allah alaih wa sallam) and the enmity of the West towards the Prophet (salla Allah alaih wa sallam) exists because of the deep malice and hatred they have been indoctrinated by the Church and the religious people. The most prominent reason for that malice is their strong fear of Islam's spread in their countries.